Enhancing English Learning Outcomes with Joyful Learning-Based Wordwall Media in Primary Schools - Dahniar, Nur (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study examines the implementation of Joyful Learning-based Wordwall media aimed at enhancing English learning outcomes among primary school students. Employing a quasi-experimental design, the research involved 60 participants, randomly divided into an experimental group that utilized Wordwall for interactive learning and a control group that engaged in traditional teaching methods over an eight-week period. Quantitative data were collected through pre- and post-intervention assessments measuring English proficiency, while qualitative data were gathered from student feedback via questionnaires and focus groups. The results indicated a significant improvement in English learning outcomes among the experimental group, with average scores increasing from 65.4 to 82.7, contrasted with a minor increase in the control group from 64.5 to 68.2. Qualitative feedback revealed that 85% of students found the Wordwall activities enjoyable and engaging, fostering greater participation and collaboration. These findings highlight the critical role of integrating technology-driven, gamified learning tools in primary education, not only to bolster academic performance but also to enhance student motivation and engagement. The study advocates for broader adoption of interactive educational technologies and ongoing teacher training to create enriching learning environments in language education.